Circular RNA: new star, new hope in cancer - Zikang Zhang; Qing Xie; Dongmei He; Yuan Ling; Yuchao Li; Jiangbin Li; Hua Zhang (BMC Cancer, 2018)
Abstract Background Circular RNAs are a new class of endogenous non-coding RNA that can function as crucial regulators of diverse cellular processes. The diverse types of circular RNAs with varying cytogenetics in cancer have also been reported. Main body of the abstract Circular RNAs can act as a microRNA sponge or through other mechanisms to regulate gene expression as either tumor inhibitors or accelerators, suggesting that circular RNAs can serve as newly developed biomarkers with clinic implications. Here, we summerized recent advances on circular RNAs in cancer and described a circular RNA network associated with tumorigenesis. The clinical implications of circular RNAs in cancer were also discussed in this paper. Short conclusion Growing evidence has revealed the crucial regulatory roles of circular RNAs in cancer and the elucidation of functional mechanisms involving circular RNAs would be helpful to construct a circRNA-miRNA-mRNA regulatory network. Moreover, circular RNAs can be easily detected due to their relative stability, widespread expression, and abundance in exosomes, blood and saliva; thus, circular RNAs have potential as new and ideal clinical biomarkers in cancer.